Fiscal federalism - an international comparison - Bernhard Seidel; Dieter Vesper (Deutsches Institut für Wirtschaftsforschung (DIW), 1999)
In federal systems, the powers and responsibilities must be divided up between central government and individual states in such a way as to enable the center effectively to carry out its duties for the nation as a whole, while allowing the lower levels of government to pursue their own regional goals at the same time. Thus, the main challenge is to find the best way to combine the advantages and disadvantages of centralization and decentralization respectively. In principle, there are two opposing normative models of organizing domestic fiscal relations. The first of these models is primarily inspired by distributive goals. Accordingly, revenue sharing is used as a tool to adjust "unequal" living conditions. This approach is exemplified by Germany, where the federal division of labor allows the lower levels of government very little discretion with regard to generating revenue. On the expenditure side, the system is characterized by an elaborate framework of domestic fiscal relations. Frequently, powers and responsibilities are shared by various levels of government, which regulary results in lengthy negotiations before the necessary broad-based consensus can be reached. There are many responsibilities that cannot be discharged independently. Equally, the extent of leveling is considerable.
Keywords: 330; Föderalismus; Finanzföderalismus; Vereinigte Staaten; Deutschland; Kanada; Schweiz